A Case of Eccrine Nevus - Kang, Min Ju (Ann Dermatol, 2008)
Eccrine nevi are very rare cutaneous lesions which may or may not be accompanied by localized hyperhidrosis. Histological findings usually reveal a slightly increased number of eccrine glands without any other abnormalities. Herein we present a case of eccrine nevus not associated with localized hyperhidrosis on the left wrist of a 6-year-old girl. The lesion was a brownish, ovoid plaque approximately 1.0 × 1.5 cm in size, with a hyperkeratotic, slightly scaly papule in the center. It was treated by surgical excision.